Artemisia annua increases resistance to heat and oxidative stresses, but has no effect on lifespan in Caenorhabditis elegans - Seung-Il OH (Food Science and Technology, 2016)
Abstract It is suggested that oxidative stress induced by cellular reactive oxygen species is one of the major causal factors of aging. The effect of dietary supplementation of anti-oxidants on response to environmental stressors and lifespan has been studied in various model organisms. In the present study, we examine the effect of Artemisia annua extract on resistance to oxidative, heat, and ultraviolet stresses in the nematode Caenorhabditis elegans. Artemisia annua significantly increases survival under oxidative and heat stresses, however has no effects in response to ultraviolet stress. Then, we measured the in vivo changes in expression of stress-responsive genes by Artemisia annua using green fluorescence protein. The expression of hsp-16.2, known to be involved in response to heat stress, is significantly increased by Artemisia annua supplementation. An anti-oxidant gene, sod-3, was also up-regulated by Artemisia annua. However, both mean and maximum lifespan of Caenorhabditis elegans was not altered by dietary supplementation of Artemisia annua. These findings indicate that Artemisia annua confers health-promoting effects through increasing the resistance to environmental stressors and has no effect on lifespan in C. elegans. Our study suggests that Artemisia annua can be used for the development of novel natural therapeutics for diseases caused by environmental stressors.